PROBLEMATICS OF THE IMPLEMENTATION OF THE EMANCIPATED CURRICULUM (IKM) IN INDONESIAN LANGUAGE OF CLASS X - Ahmad Imdadus Syarochil; Machrus Abadi (Jurnal Pendidikan (Teori dan Praktik), 2023)
This study aims to describe the problems and solutions to problems when implementing IKM, especially in the Indonesian language subject, which is one of the mandatory subjects that must be mastered by students in Indonesia. This research is in the form of descriptive qualitative research with data collection methods in the form of interviews, documentation, and simple random sampling techniques. From the research that has been done, it concludes that the problems experienced are related to technical problems in implementing the curriculum due to a lack of preparation with this new curriculum change, such as the absence of definite textbooks, being stuck with the previous curriculum, and the lack of facilities and infrastructure such as Wi-Fi networks that is not the stable and inadequate number of projectors. While the solutions that can be implemented are less effective and only temporary solutions if applied in the long term, so they require more mature preparation for the future.